Effect of specific exercise strategy on strength and proprioception in volleyball players with infraspinatus muscle atrophy - Salles, J. I.; Rodrigues Amaral Cossich, V.; Guimaraes, J. M.; Motta Filho, G.; Morrissey, D. (Scandinavian Journal of Medicine & Science in Sports, 2018)
Infraspinatus muscle atrophy is common in professional volleyball players, but it is unclear whether commonly observed strength and proprioception deficits can be reversed with training. Fifty-four participants were recruited into an infraspinatus atrophy group (IAG, n = 18) and a non-atrophy group (NAG, n=18) of elite volleyballers plus a healthy non-athletic control group (CG, n = 18). IAG were trained with a progressive, specific shoulder external rotator strengthening routine for 32 sessions over 8 weeks. Shoulder external rotation peak torque (SERPT) and threshold to detect passive movement (TTDPM) and joint position sense (JPS) were measured before and after the intervention. At baseline, no significant difference was detected in strength or proprioception between the injured and control groups, but the normal athletes were stronger and had better proprioception than either IAG or CG (p < 0.001). IAG (d = 2.78) and NAG (d = 0.442) improved strength significantly after training. IAG improved TTDM and JPS (p < 0.001, d = - 0.719 and -2.942, respectively) but were still worse than NAG (p < 0.001). Elite volleyball players with Infraspinatus muscle atrophy have strength and proprioception deficits which can be improved by a specific exercise program to normal but not elite athlete control levels.